ANALISIS FAKTOR PENYEBAB KETIDAKTERCAPAIAN KRITERIA KETUNTASAN MINIMAL DALAM PEMBELAJARAN SOSIOLOGI SISWA KELAS XII IIS - Sudaryono, Martinus Arief; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis: ‘The Analysis of The Cause Factors of The Unattainable Standard Minimum Criteria on Sociology Learning at The Students of Class XII IIS 1 at SMAN 2 Pontianak’. The purpose of this study was to determine the cause factors of the unattainable standard minimum criteria on sociology learning. The research was conducted by using qualitative approach with descriptive research method. The techniques of data collection were observation techniques, interviews and documentation studies while data collection tools were observation guidelines, interview guidelines, field notes and documents. The result of study about the cause factors of the unattainable standard minimum criteria on sociology learning at the students of class XII IIS 1 at SMAN 2 Pontianak based on the use of curriculum 2013, was collected as follows: (1) the lesson plan factor of sociology learning is the cause ; the purpose, the method and media which were inappropriate with the actual plan, (2) the lesson implementation factor of learning sociology learning is the cause; the students lack of readiness, interest and active as well as the teacher is less motivating (3) the lesson evaluation factors of sociology learning is not the cause ; the problem has been presented well from the appropriateness and difficulties of material, construction and the language used is easy to understand. Key Words : Unattainable Standard Minimum Criteria, Sociology Learning